2017
DOI: 10.2135/cropsci2017.01.0029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci for Popping Traits and Kernel Characteristics in Sorghum Grain

Abstract: Popped grain sorghum [Sorghum bicolor (L.) Moench] has developed a niche among specialty snack‐food consumers. In contrast with popcorn (Zea mays L.), sorghum has not benefitted from persistent selective breeding for popping efficiency and kernel expansion ratio. Although recent studies have already demonstrated that popping characteristics are heritable in sorghum, the discovery of quantitative trait loci (QTL) for these traits could help expedite and streamline the breeding process. To that end, the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Samples were popped in a residential air popcorn popper (Presto Orville Redenbacher's ® Hot Air Popper) for 2 min at roughly 204 • C. The hot-air poppers were modified to include a mesh screen that kept the sorghum kernels (both popped and unpopped) from blowing out during the popping assay [15]. Because slight variation does occur between poppers, two poppers were used, and each sample was popped twice in each popper for a total of four popping assays.…”
Section: Popping Evaluationmentioning
confidence: 99%
“…Samples were popped in a residential air popcorn popper (Presto Orville Redenbacher's ® Hot Air Popper) for 2 min at roughly 204 • C. The hot-air poppers were modified to include a mesh screen that kept the sorghum kernels (both popped and unpopped) from blowing out during the popping assay [15]. Because slight variation does occur between poppers, two poppers were used, and each sample was popped twice in each popper for a total of four popping assays.…”
Section: Popping Evaluationmentioning
confidence: 99%
“…Pugh et al. (2017a) and Pugh et al (2017b) found that both popping efficiency and expansion ratio were moderate to highly heritable and reported several quantitative trait loci associated with popping efficiency and expansion ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Murty et al (1988) reported that expansion ratio in pop sorghum is under polygenic control, with prominent dominance and additive gene effects. Pugh et al (2017a) and Pugh et al (2017b) found that both popping efficiency and expansion ratio were moderate to highly heritable and reported several quantitative trait loci associated with popping efficiency and expansion ratio.…”
mentioning
confidence: 99%